PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK - Fauzana Ismalna, (2022)
This research is a quantitative study that aims to determine the effect of institutional ownership, managerial ownership, and audit committee on tax avoidance. Tax avoidance was measured using Book Tax Difference (BTD). The sample in this study was 44 Cyclicals and Non-Cyclicals companies listed on the Indonesia Stock Exchange, especially the main board in the 2018-2020 period. Hypothesis testing in this study used multiple linear regression analysis with panel data regression with the help of STATA version 16 program with a significance level of 5%. The results of the test show that (1) institutional ownership has no effect on tax avoidance, (2) managerial ownership has no effect on tax avoidance, and (3) the audit committee has no effect on tax avoidance.